Genetic control of feeding preferences in the mosquitoes Aedes (Stegomyia) simpsoni and aegypti - Mukwaya, L. G. (Physiological Entomology, 1997)
The biting rate of a non‐anthropophilic (Bwayise) population of Aedes simpsoni was found to be approximately 0.3 mosquitoes per catcher per hour, whereas that of an anthropophilic (Bwamba) population was approximately 101 per catcher per hour. Population density indices, as determined by the number of pupae per wet plant axil, were 0.70 in Bwayise and 1.00 in Bwamba. The big difference in anthropophilic behaviour between these populations was therefore unlikely to be derived from this small population difference. Larval density was higher at Bwamba than at Bwayise, but isolation or crowding of the larvae in the laboratory did not affect the biting behaviour of adult Ae. simpsoni. Laboratory studies also failed to confirm field observations that temperature might play a part in determining anthropophily and non‐anthropophily in this species. In choice‐chamber landing tests, using a rat and a human hand, Ae. simpsoni females derived from wild larvae and reared in the laboratory showed that 83% of the Bwamba strain landed on man, whereas only 38% of the Bwayise strain did so. In Aedes aegypti, 71% of a long‐established laboratory strain (Ilobi) landed on man, whereas 47% of a relatively non‐anthropophilic wild (Kampala) strain did so. These preferences persisted in culture. Selective breeding increased the preference for the rodent significantly in the Kampala strain of Ae. aegypti, but had no significant effect on the Ilobi strain. Crossbreeding showed that the F1 and F2 hybrids between the anthropophilic and non‐anthropophilic strains were intermediate in their preference between the parental pure bred strains; the reciprocal crosses were not significantly different from each other. The behaviour of the backcross progenies, at least in Ae. aegypti, appeared to indicate that the genotype of the male parent might be the main determining factor.